Single incision mini sling for the treatment of urodynamic stress incontinence: Surgical outcomes and preoperative predictors of failure - Tsia-Shu Lo; Fazlin Harun; Sandy Chua; Lan-Sin Jhang; Wu-Chiao Hsieh; Yi-Hao Lin (Taiwanese Journal of Obstetrics & Gynecology, 2024)
Objective: To evaluate the surgical outcomes and predictors of failure of Single Incision Mini Sling (Ophira) in women with urodynamic stress incontinence. Materials and methods: Records of 115 women underwent anti-incontinence procedure using Ophira Mini Sling from June 2019 to September 2020 reviewed. Subjective evaluation was assessed using validated IIQ-7, UDI-6, POPDI-6 and PISQ-12 questionnaires. Multichannel urodynamics, 1-h pad test and 72-h voiding diary was performed as objective evaluation. Primary outcome was the objective cure rate of negative urine leak on provocative filling cystometry and 1-h pad test weight <2 g, and subjective cure rate was negative response to question 3 of UDI-6. Secondary outcome was to identify risk factors associated with failure for Ophira. Results: Total of 108 women were evaluated. The objective cure rate was 91.7% with subjective cure rate of 86.1%. Comparison of clinical outcome shows significant improvement of USI post-operatively (p < 0.001) and reflected in 1-h pad test (p < 0.001). Improvement in all subjective evaluation parameters is seen except for POPDI-6. Failure of Ophira correlate significantly in women age >66 years, presence of asthma, pre-operative Intrinsic Sphincter Deficiency (ISD), and Maximum Urethral Closure Pressure (MUCP) value < 40 cmH20. Conclusion: Ophira Single Incision Mini Sling is safe and effective treatment option for USI, showing high objective and subjective cure rates with low incidence of complications. Non-modifiable risks of age ≥66 years, asthma status, pre-operative intrinsic sphincteric deficiency and low maximal urethral closure pressure were the factors of failure for Ophira.